Using Kids Song to Improve Students’ Listening Skills at SMPN 5 Padang - Almaidah Shapitri (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2020)
The research questions of this study are: what is the effect of learning to listen using children's songs in class VII SMPN 5 Padang for the 2020/2021 academic year. And how to increase students' understanding of listening skills through children's songs in grade VII at SMPN 5 Padang for the 2020/2021 school year. This research is done to determine the effect of children's songs on improvement listening skills, and to find out how English nursery rhymes can improve their hearing comprehension. In obtaining these data, the authors conducted pre-experimental research at SMP 5 Padang involving 32 students in the class. The author uses one type pre-experimental teaching, namely the pre-test and posttest design of one group. The results showed that there was a significant increase understand students' hearing by using songs as the medium. This is found by comparing the pre-test and post-test scores. Score The pre-test mean score was 3.32, while the post-test mean score was 8.22. Based on the data obtained, the authors concluded that their auditory comprehension improves after being taught use children's songs as a medium, they are also interested and motivated in the learning process. And using songs as a medium to improve their listening really makes them active in class.